(3GdfLe GdhgGL aj TQM GdefgGLs - (3eMeO Hf ehSi Hf YjSi GdOejQj GdTGaYj , ceGd GdOjf CHh GdHbGA,J (B808 (3g` s; (3Gdfhhj,J (B676 (3g` s
(3ChdgG (B:s
(3cJGH GdUOGb s
(3fSNI NGeSIs
(3hYdjg ELGRI HNW GdeDda dJGL GdOjf eMeO Hf GdeUQis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdTGaYjs